Does Global Value Chain Embeddedness Matter for the Green Innovation Value Chain? - Hu, Dianxi; Jiao, Jianling; Chen, Chuxi; Xiao, Renqiao; Tang, Yunshu (Frontiers in Environmental Science, 2022)
The global value chain (GVC) is a new model of international commodity manufacturing and trade that provides a unique channel to obtain innovative knowledge and technology spillover. However, the impact mechanism of GVC embeddedness on the internal processes of the green innovation value chain (GIVC) is not clear. This study opens the “black box” of green innovation processes, which is very important for connecting resource and industrial chains. The KPWW method and the super-efficiency network SBM-DEA model (NSBM-S) are used to measure the GVC embeddedness index and GIVC efficiency, respectively. A panel model is constructed to demonstrate the multidimensional impacts of the GVC position on GIVC. The result show mean green technology R&D efficiency is less than mean green achievement transformation efficiency; the impact of the GVC embeddedness on the GIVC efficiency is mainly reflected in the rise of the GVC position rather than the deepening of GVC participation; and the impact of the rise of the GVC position on the green technology R&D efficiency is greater than that of green achievement transformation efficiency. Without considering the greenness characteristics of intermediate output, the impact of the GVC position on the general innovation value chain will be amplified. Our conclusions are conducive to identifying the weak links in green innovation processes and provide novel empirical evidence for formulating sustainable development countermeasures in an open economy.